PENDAMPINGAN MASYARAKAT DALAM PENYUSUNAN MASTERPLAN OBJEK WISATA EMBUNG KLEDUNG, KABUPATEN TEMANGGUNG - Ardiana Yuli Puspitasari (UNISSULA Semarang, 2022)
Embung Kledung is a tourist attraction that utilizes the natural potential of Mount Sumbing and Mount Sindoro so that it is able to offer very beautiful natural scenery accompanied by cool weather. Embung Kledung is located in Kledung Village, Kledung District, Temanggung Regency. Currently the Embung Kledung tourist attraction is managed by the village youth group